Atendimento psicoterápico à comunidade universitária externa - Herrera, Lara Giacometti [UNESP]; Dionísio, Gustavo Henrique [UNESP]; Coelho, Amanda Oliveira [UNESP]; Sabbadini, Aline [UNESP]; Capellanes, Laura Moreno Lima [UNESP]; Gerolamo, Joselene Cristina [UNESP]; Lima, Jéssica Balatori de [UNESP]; Oliveira, Letícia de Moraes [UNESP]; Hikita, Patrícia Haruko [UNESP]; Cruz, Reinaldo Pereira da [UNESP]; Fenolio, Fernanda Flacon [UNESP]; Passarinho, José Guilherme Nogueira [UNESP]; et al. (Universidade Estadual Paulista (Unesp), 2015)
This project exists for four and a half years, linked to PROEX (Pró-Reitoria de Extensão Universitária) that craves the possibility to enable the free expirience of a therapeutic process to college students that belongs to the external community of FCL/UNESP (Faculdade de Ciências e Letras de Assis-SP) or to its ex college students. The main objectiv of the project refers to gains in mental health to the main public, attend the demand of this specific public and also to enable the experience of conducting the therapeutic process to the graduating students of the project. From the project, it became interesting to think about how it would be the transferencial relationship between therapist and pacient, being both college students.

Projeto existente há 4 anos e meio, vinculado à PROEX – Pró-Reitoria de Extensão Universitária que visa possibilitar a experiência gratuita de um processo terapêutico a universitários pertencentes à comunidade externa da FCL/UNESP – Faculdade de Ciências e Letras de Assis-SP ou a ex-alunos da mesma. O objetivo principal do projeto se refere a ganhos em saúde mental do público-alvo, atender a demanda deste público em específico e possibilitar, também, a experiência da condução do processo terapêutico aos participantes graduandos do projeto. A partir do projeto, tornou-se interessante pensar sobre como se daria a relação transferencial entre terapeuta e paciente neste caso, ambos compartilhando da mesma situação de universitários.
Keywords: Free psychotherapy; University; Psychoanalysis; Psicoterapia gratuita; Universitários; Psicanálise